Proceedings of the Seventh International Workshop on Petri Nets and Performance Models
DOI: 10.1109/pnpm.1997.595535
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state analysis of infinite stochastic Petri nets: comparing the spectral expansion and the matrix-geometric method

Abstract: In this paper we investigate the eficiency of two solution approaches to infinite stochastic Petri nets: the matrix-geometric method and the spectral expansion method. W e first informally present infinite stochastic Petri nets, after which we describe, using uniform notation, the matrix-geometric and the spectral expansion method. W e put special emphasis on the numerical aspect of the solution procedures. Then, we investigate the suitability of these approaches t o account for batch-movements of tokens. W e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…It is confirmed by a number of works that the spectral expansion method is better than the matrix geometric method in a number of aspects [5,32,33,39]. It is observed that the spectral expansion method is proved to be a mature technique for the performance analysis of various problems [5-17, 20-25, 27, 28, 31, 32, 38, 39, 49-51, 53, 54, 52, 58].…”
Section: Introductionmentioning
confidence: 95%
“…It is confirmed by a number of works that the spectral expansion method is better than the matrix geometric method in a number of aspects [5,32,33,39]. It is observed that the spectral expansion method is proved to be a mature technique for the performance analysis of various problems [5-17, 20-25, 27, 28, 31, 32, 38, 39, 49-51, 53, 54, 52, 58].…”
Section: Introductionmentioning
confidence: 95%
“…Mitrani and Chakka [MIT95] compare the performance of the spectral expansion and matrix-geometric methods for an M/M/c-type queue. Haverkort and Ost [HAV97] also compare the spectral expansion method with the Latouche-Ramaswami algorithm for a model of a fault-tolerant system. Tran and Do [TRA00] present a comparison of the practical performance of matrix-geometric methods and of the spectral expansion for a specific quasi birth-and-death process.…”
Section: Inriamentioning
confidence: 99%
“…The latter arrive according to an independent Poisson process with rate ξ. When a fault occurs, the system instantaneously rolls back to the last established checkpoint; all transactions which arrived since that moment either remain in the queue, if they have not been processed, or return to it, in order to be processed again (it is assumed that repeated service times are resampled independently) (see [11,8]). This system can be modelled as an unbounded queue of (uncompleted) transactions, which is modulated by an environment consisting of completed transactions and checkpoints.…”
Section: Checkpointing and Recovery In The Presence Of Faultsmentioning
confidence: 99%
“…More recently, Grassmann [7] has discussed models where the eigenvalues can be isolated and determined very efficiently. Some comparisons between the spectral expansion and the matrix-geometric solutions can be found in [16] and in Haverkort and Ost [8]. The available evidence suggests that, where both methods are applicable, spectral expansion is faster even if the matrix R is computed by the most efficient algorithm.…”
Section: Introductionmentioning
confidence: 99%